2017
DOI: 10.5301/uro.5000214
|View full text |Cite
|
Sign up to set email alerts
|

Symplastic glomus tumor of the urinary bladder treated by robot-assisted partial cystectomy: a case report and literature review

Abstract: Glomus tumors arising in the urinary bladder are extremely rare, and only two cases have been reported in the English Literature. We present a case of a 58-year-old man with an asymptomatic mass of the anterior wall of the bladder that measured 2.5 × 2.5 cm. Endoscopic excision was performed, and the tumor was diagnosed as symplastic glomus tumor. The patient finally underwent robotic-assisted partial cystectomy, and he remains healthy without any recurrence to date. After reviewing this case and previous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…We can refer to the treatment of GTs that occurred in other organs to make the therapy plan. Transurethral resection of bladder tumor (TURBt) is an effective method for benign ( 22 ) or undetermined malignant potential ( 23 ) GTs of the bladder. Malignant GTs are highly aggressive with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We can refer to the treatment of GTs that occurred in other organs to make the therapy plan. Transurethral resection of bladder tumor (TURBt) is an effective method for benign ( 22 ) or undetermined malignant potential ( 23 ) GTs of the bladder. Malignant GTs are highly aggressive with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha publicado también la presencia de células neoplásicas por fuera del límite de la lesión 15,16 . En los hallazgos citológicos de reportes de casos se han observado células agrupadas, uniformes, con núcleos circulares a ovalados y escaso citoplasma 17 .…”
Section: Discussionunclassified
“…GT occurring in the bladder is very rare and has been reported sporadically. To the best of our knowledge, only 4 cases of bladder GT have been previously identified in studies reported in English [2][3][4][5]. The present study aimed to (1) present an extremely rare case of GT in the bladder and (2) summarize its clinical and histopathologic features by literature review.…”
Section: Introductionmentioning
confidence: 96%